Barriers to Nurses’ Promoting Mobility in Hospitalized Older Adults - (:unkn) unknown (My University, 2016)
Objectives: To examine the association between nurses’ knowledge, attitude and external barriers and the nurse’s mobility-promoting behavior. Nurse perception of the priority organizations place on mobility, and the relationship of nurses’ level of experience to nurse prioritization for promoting mobility was also investigated. Design: Cross-sectional, descriptive, correlation study with convenience sampling. Setting: Two community-based hospitals in the Pacific Northwest of the U.S. Participants: Eighty-five nurses caring for 98 inpatients 65 and older. Measurement: Nurses’ knowledge, attitude and external barriers were examined with a validated 5-point Likert Scale. Patient-related and other clinical barriers and the nurses mobility-promoting behavior was obtained with the validated self-recorded mobility log. Patient Basic Metabolic Index (BMI) and severity of illness was obtained though data extraction. Results: Nurses viewed the promotion of mobility as important, yet mobilizing older patients was infrequent. Nurses perceived a number of barriers to promoting mobility: Patient condition, the perception that patients could be harmed during mobilization, perceptions of heavy workload, difficulty prioritizing nursing care, and staffing shortages. While novice nurses had lower priority to promote mobility compared to more experienced nurses, novice nurses tended to promote more mobility. Conclusion: As nurses care for hospitalized older adults the convergence of interpersonal, patient, and environmental complexities acting as barriers to mobility need to be considered. It is important to understand the needs of beginning, less experienced nurses to overcome the barriers to promoting mobility. This study shows that even experienced nurses need to overcome barriers to promoting mobility. Hospitals need to address the needs of the novice nurse while enhancing the practice of more experienced nurses in order to support nurse-promoted mobility. The findings from this study show that nurses knowledge, attitude, and external barriers could play a role in the low levels of mobility in hospitalized older adults.
Keywords: Barriers; Hospitalization; Mobility; Nurses; Older Adults